Impact of coeval tectonic and sedimentary-driven tectonics on the development of overpressure cells, on the sealing, and fluid migration –Petroleum potential and environmental risks of the Makran Accretionary Prism in Pakistan - Ellouz-Zimmermann, N; Battani, A; Deville, E; Prinzohfer, A; Ferrand, J (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1253 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.50-51.